A preparation method of a tellurium and nitrogen co-doped rape straw derived carbon electrocatalyst
Patent Information
- Application Number
- CN202611498283.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]为解决现有技术中的上述问题,本发明提供了一种碲、氮共掺杂油菜秆衍生碳电催化剂的制备方法,有效解决了油菜秸秆衍生碳比表面积小、孔隙率低、活性位点不足、氧还原催化性能差等问题
本发明以农林废弃物油菜秸秆为碳源,通过草酸铵与碲粉协同活化两步热解制备碲、氮共掺杂多孔石墨碳材料,实现了生物质基碳材料的结构调控与电催化性能提升。与直接热解、单一草酸铵活化或单一碲掺杂及一步热解制备工艺相比,草酸铵与碲粉的协同作用可显著提高材料比表面积与孔隙率,构建丰富介孔结构以促进氧还原反应的传质过程,并有效暴露活性位点。同时实现高效氮掺杂与碲元素原位键合,形成高活性Te-N-C结构,其中以石墨氮为主的掺杂组态不仅提升衍生碳自身导电性能,还能够促进碲元素的原位键合以显著提升氧还原反应的催化活性。本发明的碲、氮共掺杂油菜秸秆衍生碳电催化剂表现出更高的起始还原电位和极限扩散电流密度,氧还原反应遵循四电子转移路径,高效地反应为水,催化性能优异,可与商业Pt/C催化剂相媲美。本发明原料来源广泛、成本低廉、制备工艺简单绿色,实现了生物质资源化高值利用,所制得的多孔碳材料在燃料电池、金属-空气电池等氧还原电催化领域具有良好的应用前景。
Smart Images

Figure CN123018006A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy electrode materials technology, and particularly relates to a tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst, its preparation method and application. Background Technology
[0002] Carbon materials, with their advantages of large specific surface area, tunable pore structure, excellent electrical conductivity, abundant precursor reserves, and superior mechanical strength, have found widespread application in electrocatalysis. Early carbon-based materials used in electrocatalysis systems were mainly carbon nanotubes and graphene. The raw materials for these materials largely rely on non-renewable fossil resources, and the synthesis processes require stringent conditions such as arc discharge, laser ablation, and chemical vapor deposition. Furthermore, the number of active sites in the original carbon framework is limited, necessitating heteroatom doping to enhance catalytic activity. Therefore, existing carbon nanomaterials suffer from drawbacks such as high production costs, low product yields, complex synthesis equipment, high energy consumption in the preparation process, and a tendency to cause a series of environmental pollution problems.
[0003] Agricultural waste, as a abundant and widely available carbon-rich renewable resource, is an ideal precursor for the preparation of carbon-based electrocatalysts. Low-cost biomass-derived carbon materials can be obtained simply through high-temperature pyrolysis, providing a feasible solution to the problems of non-renewable traditional nano-carbon raw materials and high pollution during preparation. However, biomass-derived carbon materials prepared by direct pyrolysis generally suffer from inherent defects such as small specific surface area, underdeveloped pore structure, scarce surface active sites, and poor intrinsic electrocatalytic activity, failing to meet the requirements of efficient electrocatalytic reactions. Currently, activation pore formation and heteroatom doping are the two mainstream modification techniques for improving the catalytic performance of biomass-derived carbon materials. Conventional activation processes often use reagents such as KOH, ZnCl2, Na2CO3, and K2CO3. These activators are highly corrosive, severely corroding reaction equipment during preparation, and the resulting waste liquid and residue can easily cause secondary ecological pollution. Furthermore, activation and doping are often separate and independent processes, resulting in lengthy and complex processes with high energy and time costs, making industrial-scale production difficult.
[0004] In existing technologies, studies have employed ammonium oxalate to activate dandelion-derived nitrogen-doped carbon materials and apply them to the electrocatalytic oxygen reduction reaction. This method uses dandelion straw as a carbon source and ammonium oxalate as an activator, preparing nitrogen-doped carbon-based electrocatalysts through high-temperature pyrolysis at 1100℃. The oxygen reduction catalytic performance is optimized by activating and expanding pores, increasing the degree of graphitization, and enriching pyridine nitrogen and graphitic nitrogen active sites. Chinese invention patent application CN202110769806.7 discloses a tellurium-doped oxygen reduction catalyst and its preparation method. This catalyst uses tellurium nanowires, dopamine hydrochloride, and heme chloride as raw materials, and prepares a tellurium-doped Fe-NC oxygen reduction catalyst through ammonia-assisted nitrogen doping and high-temperature pyrolysis. Although the above technologies improve catalytic performance by controlling the surface composition and doping structure of the materials, they still have significant shortcomings: excessively high pyrolysis temperature, difficulty in obtaining raw materials, and cumbersome and complex preparation processes, making it difficult to simultaneously achieve low cost, greenness, and high efficiency.
[0005] Based on the current state of technology, biomass-derived carbon materials still face many key technological bottlenecks in oxygen reduction electrocatalysis applications: low specific surface area of direct pyrolysis products, underdeveloped pore structure, insufficient number of active sites, low doping efficiency, and poor electrical and mass transfer capabilities; single activation or single-atom doping cannot simultaneously achieve the synergistic construction of high specific surface area, hierarchical pore structure, and efficient active sites, resulting in electrocatalytic performance far inferior to commercial Pt / C catalysts, failing to meet practical application requirements. Meanwhile, existing modification technologies generally suffer from complex processes, high costs, and low biomass resource utilization rates.
[0006] Current technologies for carbon materials derived from rapeseed straw, a typical agricultural waste, still face core challenges such as small specific surface area, low porosity, lack of active sites, and poor oxygen reduction catalytic performance. Therefore, developing a simple, low-cost, and environmentally friendly synergistic activation and modification method to simultaneously optimize the pore structure of rapeseed straw-derived carbon materials and precisely construct highly active Te-NC sites is crucial for preparing high-performance, low-cost non-precious metal oxygen reduction electrocatalysts. This approach is of significant practical importance for enhancing the resource utilization value of agricultural waste and promoting the industrial application of efficient non-precious metal electrocatalysts. Summary of the Invention
[0007] To address the aforementioned problems in the prior art, this invention provides a method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalysts, effectively solving the problems of small specific surface area, low porosity, insufficient active sites, and poor oxygen reduction catalytic performance of rapeseed straw-derived carbon. Simultaneously, this invention employs a green synergistic activation method to simultaneously optimize the pore structure and construct highly active Te-NC sites, resulting in a low-cost, high-performance non-precious metal oxygen reduction electrocatalyst.
[0008] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of the present invention: This invention provides a method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalysts, comprising the following steps: (1) After crushing the rapeseed straw, mix it with water and place it in a sealed container for heat preservation treatment. Then take it out, wash and dry it to obtain carbonaceous solid product. (2) The carbonaceous solid product is mixed with tellurium powder and then subjected to a first pyrolysis treatment; (3) The product after the first pyrolysis treatment is mixed with ammonium oxalate and subjected to a second pyrolysis treatment to obtain the electrocatalyst.
[0009] Furthermore, the mass ratio of rapeseed straw to water in step (1) is 1:25.
[0010] Furthermore, the temperature of the heat preservation treatment in step (1) is 185-195℃ and the heat preservation time is 12-24h. This temperature can ensure that the rapeseed straw powder is properly dried and that the powder does not clump together. The drying temperature is 80℃, and the drying time is 8-12 hours.
[0011] Furthermore, the mass ratio of the carbonaceous solid product to tellurium powder in step (2) is 1: (0.5-1.5).
[0012] Furthermore, the conditions for the first pyrolysis treatment in step (2) are to raise the temperature to 500°C under nitrogen protection and maintain it for 0.5 h.
[0013] Beneficial effects: Tellurium has a melting point of 450℃, and a pyrolysis temperature of 500℃ ensures that it melts into a liquid, allowing it to effectively and fully contact the rapeseed straw powder, thus maximizing its effectiveness in subsequent processing. Temperatures of 600℃ will result in tellurium loss, affecting its role in the pyrolysis process.
[0014] Furthermore, the mass ratio of the product after the first pyrolysis treatment in step (2) to ammonium oxalate is 1:(1-3), preferably 1:2.
[0015] Beneficial effects: Ammonium oxalate not only provides a nitrogen source in the preparation of derivatized carbon catalysts, but also acts as an activator. During heating, it decomposes into gas, which is used to expand the pore size and increase the specific surface area of carbon. It also acts as a nitrogen source to be incorporated into the carbon framework, thereby forming active sites and promoting the catalytic activity of carbon materials.
[0016] Furthermore, the conditions for the second pyrolysis treatment in step (2) are to raise the temperature to 850-1050℃ under nitrogen protection and maintain it for 2 hours.
[0017] Beneficial effects: The above-mentioned pyrolysis temperature can effectively promote the carbonization process of rapeseed straw, and at the same time facilitate the smooth progress of the doping process, so as to effectively control the doping amount and the state of the doping elements, thereby obtaining the best catalytic activity.
[0018] The second technical solution of the present invention: The present invention also provides an electrocatalyst prepared using the method for preparing the tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst.
[0019] The third technical solution of the present invention: The present invention also provides an application of the electrocatalyst as a cathode oxygen reduction catalyst in a fuel cell or a metal-air battery.
[0020] The beneficial effects of this invention compared to the prior art are as follows: This invention utilizes rapeseed straw, an agricultural and forestry waste, as a carbon source. It prepares tellurium-nitrogen co-doped porous graphitic carbon materials through a two-step pyrolysis process involving the synergistic activation of ammonium oxalate and tellurium powder, achieving structural regulation and enhanced electrocatalytic performance of biomass-based carbon materials. Compared to direct pyrolysis, single ammonium oxalate activation, or single tellurium doping followed by a one-step pyrolysis process, the synergistic effect of ammonium oxalate and tellurium powder significantly increases the specific surface area and porosity of the material, constructing a rich mesoporous structure to promote the mass transfer process of the oxygen reduction reaction and effectively exposing active sites. Simultaneously, it achieves efficient nitrogen doping and in-situ bonding with tellurium, forming a highly active Te-NC structure. The doping configuration, dominated by graphitic nitrogen, not only enhances the conductivity of the derived carbon itself but also promotes in-situ bonding of tellurium, significantly improving the catalytic activity of the oxygen reduction reaction. The tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst of this invention exhibits higher onset reduction potential and limiting diffusion current density. The oxygen reduction reaction follows a four-electron transfer pathway, efficiently converting to water, demonstrating excellent catalytic performance comparable to commercial Pt / C catalysts. This invention utilizes widely available and inexpensive raw materials, employing a simple and environmentally friendly preparation process, achieving high-value utilization of biomass resources. The resulting porous carbon material shows promising application prospects in oxygen reduction electrocatalysis fields such as fuel cells and metal-air batteries. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1Figure 1 shows SEM images of the electrocatalysts prepared in Example 2 and Comparative Examples 1-4 of this invention. Figure 2(a) is an SEM image of RDC, Figure 3(b) is an SEM image of RDNC, Figure 4(c) is an SEM image of RDTeC, Figure 5(d) is an SEM image of RDTeNC-950, and Figure 6(e) is an SEM image of RDTeNC. Figure 2 The XRD patterns of the electrocatalysts prepared in Example 2 and Comparative Example 4 of this invention are shown below. Figure 3 The nitrogen adsorption-desorption isotherm (a) and pore size distribution curve (b) of the electrocatalysts prepared in Example 2 and Comparative Examples 1-4 of this invention are shown. Figure 4 The surface chemical composition and valence state analysis of the electrocatalysts prepared in Example 2 and Comparative Examples 2-4 of this invention are shown in Figure (a), which is the XPS full spectrum of the electrocatalysts prepared in Example 2 and Comparative Examples 2-4; Figure (b) is the C 1s spectrum of the electrocatalyst prepared in Example 2; Figure (c) is the N 1s spectrum of the electrocatalyst prepared in Example 2; and Figure (d) is the Te 3d spectrum of the electrocatalyst prepared in Example 2. Figure 5 The following graphs are provided: (a) CV curve of the electrocatalyst prepared in Example 2 of the present invention in N2 or O2 saturated KOH solution; (b) LSV curve of the electrocatalyst prepared in Example 2 and Comparative Examples 1-4 and commercial Pt / C for oxygen reduction reaction; (c) LSV curve of the electrocatalyst prepared in Example 2 at different rotation speeds (inset shows the number of electrons transferred at different potentials); and (d) stability comparison graph of the electrocatalyst prepared in Example 2 and commercial Pt / C. Detailed Implementation
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0028] Example 1 A method for preparing a tellurium and nitrogen co-doped rapeseed stalk-derived carbon electrocatalyst includes the following steps: (1) After washing and drying the rapeseed straw with distilled water, crush it with a pulverizer until it passes through a 100-mesh sieve to obtain rapeseed straw powder; (2) Weigh 2g of the above rapeseed straw powder and add it to 50mL of distilled water and stir thoroughly. Transfer the mixture to a high-pressure reactor and place it in an oven. Keep it at 190℃ for 12h. Then take it out and filter it and wash it with distilled water. Place it in a vacuum drying oven and dry it at 80℃ for 10h to obtain carbonaceous solid product. (3) Weigh 0.5g of the above carbonaceous solid product and 0.5g of tellurium powder, grind and mix them evenly, then place the mixture in a small magnetic boat, place the small magnetic boat in the middle of the tube furnace, heat it to 500℃ under nitrogen protection, and keep it for 0.5h to carry out the first pyrolysis treatment; (4) Weigh 0.5g of the product from the first pyrolysis treatment and 1g of ammonium oxalate, grind and mix them evenly, then place the mixture in a small magnetic boat, place the small magnetic boat in the middle of a tube furnace, heat it to 950℃ under nitrogen protection, and keep it for 2h to carry out the second pyrolysis treatment. After completion, cool it to obtain tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst.
[0029] Example 2 A method for preparing a tellurium and nitrogen co-doped rapeseed stalk-derived carbon electrocatalyst differs from Example 1 in that: the amount of ammonium oxalate added in step (4) is 2g; The remaining preparation methods are the same as in Example 1, and a tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst, denoted as RDTeNC, is obtained.
[0030] Example 3 A method for preparing a tellurium and nitrogen co-doped rapeseed stalk-derived carbon electrocatalyst differs from Example 1 in that: the amount of ammonium oxalate added in step (4) is 3g; The remaining preparation methods are the same as in Example 1.
[0031] Example 4 A method for preparing a tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst differs from Example 1 in that: in step (4), the amount of ammonium oxalate added is 2g, the temperature of the second pyrolysis treatment is 850℃, and it is maintained for 2h; The remaining preparation methods are the same as in Example 1.
[0032] Example 5 A method for preparing a tellurium and nitrogen co-doped rapeseed stalk-derived carbon electrocatalyst differs from Example 1 in that: in step (4), the amount of ammonium oxalate added is 2g, the temperature of the second pyrolysis treatment is 1050℃, and it is maintained for 2h; The remaining preparation methods are the same as in Example 1.
[0033] Comparative Example 1 (only one pyrolysis treatment) A method for preparing a tellurium and nitrogen co-doped rapeseed stalk-derived carbon electrocatalyst includes the following steps: (1) After washing and drying the rapeseed straw with distilled water, crush it with a pulverizer until it passes through a 100-mesh sieve to obtain rapeseed straw powder; (2) Weigh 2g of the above rapeseed straw powder and add it to 50mL of distilled water and stir thoroughly. Transfer the mixture to a high-pressure reactor and place it in an oven. Keep it at 190℃ for 12h. Then take it out and filter it and wash it with distilled water. Place it in a vacuum drying oven and dry it at 80℃ for 10h to obtain carbonaceous solid product. (3) Weigh 0.5g of the above carbonaceous solid product, 0.5g of tellurium powder and 2g of ammonium oxalate, grind and mix them evenly, then place the mixture in a small magnetic boat, place the small magnetic boat in the middle of a tube furnace, heat it to 950℃ under nitrogen protection and keep it for 2h, cool it after pyrolysis to obtain tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst, denoted as RDTeNC-950.
[0034] Comparative Example 2 A method for preparing a nitrogen-doped rapeseed stalk-derived carbon electrocatalyst differs from Example 2 in that: tellurium powder is not added, only ammonium oxalate is added; The remaining preparation methods are the same as in Example 2, and the prepared electrocatalyst is denoted as RDNC.
[0035] Comparative Example 3 A method for preparing a tellurium-doped rapeseed stalk-derived carbon electrocatalyst differs from Example 2 in that: ammonium oxalate is not added, only tellurium powder is added; The remaining preparation methods are the same as in Example 2, and the prepared electrocatalyst is denoted as RDTeC.
[0036] Comparative Example 4 A method for preparing a rapeseed stalk-derived carbon electrocatalyst includes the following steps: (1) After washing and drying the rapeseed straw with distilled water, crush it with a pulverizer until it passes through a 100-mesh sieve to obtain rapeseed straw powder; (2) Weigh 2g of the above rapeseed straw powder and add it to 50mL of distilled water and stir thoroughly. Transfer the mixture to a high-pressure reactor and place it in an oven. Keep it at 190℃ for 12h. Then take it out and filter it and wash it with distilled water. Place it in a vacuum drying oven and dry it at 80℃ for 10h to obtain carbonaceous solid product. (3) The above carbonaceous solid product was placed in a small magnetic boat and placed in the middle of a tube furnace. The temperature was raised to 950°C under nitrogen protection and maintained for 2 hours. After pyrolysis, the product was cooled to obtain rapeseed straw-derived carbon electrocatalyst, denoted as RDC.
[0037] Performance testing 1. The electrocatalysts prepared in Example 2 and Comparative Examples 1-4 were analyzed by scanning electron microscopy (SEM), and their SEM images are shown below. Figure 1 As shown, through Figure 1 It can be seen that the product obtained by direct pyrolysis of rapeseed straw at 950℃ exhibits a micron-sized spherical morphology. The morphology of the product changes significantly after the introduction of ammonium oxalate, forming an interwoven and aggregated nano-network structure. This phenomenon is attributed to the pore-expanding effect caused by the gas generated during the high-temperature decomposition of ammonium oxalate. The introduction of elemental tellurium can promote the matrix carbonization process of rapeseed straw, but the resulting carbon material structure is relatively dense. If tellurium powder, ammonium oxalate, and hydrothermally treated rapeseed straw are mixed and directly pyrolyzed at 950℃ to prepare an electrocatalyst, the resulting product not only has a relatively dense surface, but also only a small number of nanoparticles can be tightly attached to the surface of the electrocatalyst. However, the electrocatalyst prepared in this invention, under the combined action of tellurium and ammonium oxalate, transforms rapeseed straw into particles with a diameter of approximately 10–15 nm. These particles adhere to each other to form a short nanorod structure, accompanied by abundant hierarchical pores. This unique microstructure facilitates the full exposure of active sites, promotes electrolyte transport, and improves the efficiency of the electrocatalytic reaction.
[0038] 2. X-ray diffraction (XRD) analysis was performed on the electrocatalysts prepared in Example 2 and Comparative Example 4. The results are as follows: Figure 2 As shown, through Figure 2It can be seen that both RDC and RDTeNC possess graphene structures (PDF #75-1621), confirming that graphene carbon materials can be successfully prepared by the pyrolysis of rapeseed straw. Furthermore, RDTeNC exhibits stronger diffraction peak intensities than RDC, indicating that tellurium and nitrogen co-doping further promotes the ordered stacking of carbon layers and increases the graphitization degree of the material.
[0039] 3. Nitrogen adsorption-desorption tests were performed on the electrocatalysts prepared in Example 2 and Comparative Examples 1-4. The test method was as follows: using a specific surface area and pore size analyzer, with high-purity nitrogen as the adsorbate, the nitrogen adsorption-desorption isotherms of each sample were measured at 77K liquid nitrogen temperature. Before the test, the samples were placed under vacuum and degassed at 200℃ for 8 hours. The specific surface area of the samples was calculated using the Brunauer-Emmett-Teller (BET) method; the total pore volume was obtained by converting the adsorption amount at a relative pressure P / P0≈0.99; the average pore size was calculated at 4V / SBET; the mesopore size distribution was analyzed using the Barrett-Joyner-Halenda (BJH) method, and the micropore volume was calculated using the t-plot method.
[0040] Test results are as follows Figure 3 As shown, through Figure 3 It can be seen that the nitrogen adsorption-desorption isotherms of the electrocatalysts prepared under different pyrolysis conditions show significant differences. Among them, the RDTeNC sample exhibits the highest nitrogen adsorption capacity and displays a typical type IV isotherm and hysteresis loop, indicating that it has a rich mesoporous structure. BET calculations show significant differences in the specific surface area of each sample, with the direct pyrolysis product RDC having the lowest specific surface area, only 5.33 m². 2 / g; The introduction of ammonium oxalate alone can increase the specific surface area of the product to 63.14m². 2 / g, adding tellurium powder alone increases the specific surface area of the derived carbon to 25.05m². 2 / g. The specific surface area of the derived carbon electrocatalyst RDTeNC-950, obtained by directly pyrolyzing a mixture of tellurium powder, ammonium oxalate, and hydrothermally treated rapeseed straw at 950℃, was slightly increased to 154.72 m². 2 The concentration of 413.07 m² / g indicates that this preparation method cannot fully utilize the activation and pore-forming effects of tellurium and ammonium oxalate, thus failing to achieve ideal catalytic performance. When ammonium oxalate and tellurium powder coexist, the specific surface area of the carbon material prepared by pyrolysis is significantly increased, reaching 413.07 m². 2 / g. From Figure 3 The pore size distribution curves show that the tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst RDTeNC has a significantly higher porosity than the direct pyrolysis product, and also higher than carbon materials produced by ammonium oxalate or tellurium powder alone, with a pore volume reaching 0.27 cm³. 3 / g. The above results confirm that the synergistic effect of tellurium and ammonium oxalate can effectively regulate the pore structure of rapeseed straw-derived carbon, construct a rich mesoporous system, and thus significantly enhance the mass transport efficiency in the electrocatalytic process, fully expose more active sites, and effectively improve the electrocatalytic performance of carbon materials.
[0041] 4. The surface chemical composition and valence state of the electrocatalysts prepared in Example 2 and Comparative Examples 2-4 were analyzed by XPS characterization, and the results are as follows: Figure 4 As shown, through Figure 4 (a) It can be seen that all derived carbon materials are mainly carbon, confirming that rapeseed straw biomass has been completely carbonized. Nitrogen was detected in all four electrocatalysts, with the lowest nitrogen doping content in direct pyrolysis carbon (RDC). Ammonium oxalate, as an exogenous nitrogen source, can significantly increase the nitrogen doping content of the materials, and the introduction of tellurium can further promote the nitrogen doping process. The combined effect of the two can effectively improve the nitrogen doping level. Figure 4 The results in (b) further verify the successful realization of full carbonization and efficient nitrogen doping of rapeseed straw. Figure 4 (c) The high-resolution spectrum shows that the nitrogen species doped in the material are mainly in the form of graphitic nitrogen, which is the key site for improving electrocatalytic activity. At the same time, the appearance of the Te-N characteristic signal directly confirms that tellurium atoms achieve synergistic doping by bonding with nitrogen atoms. Figure 4 The results in (d) confirm the stable existence of the Te-NC ternary doped structure, which provides abundant and efficient active sites for electrocatalytic reactions, thus ensuring the excellent electrocatalytic performance of the material from a structural perspective.
[0042] 5. A working electrode was prepared using the RDTeNC modified electrode from Example 2. A three-electrode system was used: an Ag / AgCl electrode as the reference electrode and a platinum wire electrode as the counter electrode. 0.1M KOH was used as the electrolyte. The electrocatalytic performance of the oxygen reduction reaction (ORR) was tested using cyclic voltammetry (CV) under an oxygen / nitrogen saturated atmosphere. The results are as follows: Figure 5 As shown in (a), the tests showed that the RDTeNC-derived carbon activated by ammonium oxalate exhibited a significant oxygen reduction characteristic peak at a potential of 0.83 V (vs. RHE), with a peak current density of 1.23 mA / cm². 2 It exhibits excellent electrocatalytic response to the oxygen reduction reaction.
[0043] Polarization curves of various comparative materials obtained using the linear sweep voltammetry (LSV) method under the same testing conditions are shown below. Figure 5As shown in (b). The test results show that the initial reduction potentials (ORRs) of the direct pyrolysis product RDC, the pyrolysis product RDTeC with added tellurium powder, the pyrolysis product RDNC with added ammonium oxalate, RDTeNC-950, RDTeNC (Example 2), and commercial Pt / C are 0.87V, 0.97V, 0.96V, 0.97V, 0.99V, and 0.98V, respectively. The introduction of ammonium oxalate or tellurium powder can positively increase the initial reduction potential of rapeseed straw-derived carbon to varying degrees. The addition method of both has a significant impact on the catalytic activity of the final product. The initial reduction potential of RDTeNC-950 shifts negatively by about 20mV, and the limiting diffusion current is relatively low. The RDTeNC carbon material obtained by synergistic activation of both has a higher initial reduction potential, comparable to commercial Pt / C, and the limiting diffusion current is significantly better than the other comparative carbon materials and comparable to commercial Pt / C, fully demonstrating its excellent oxygen reduction electrocatalytic performance.
[0044] The LSV curves of the RDTeNC prepared in Example 2 under the same test conditions at different rotational speeds are as follows: Figure 5 As shown in (c). The results show that the initial reduction potential of the sample remains stable with increasing electrode rotation speed, while the limiting diffusion current increases systematically. Calculations indicate that the number of electrons transferred by oxygen molecules on the catalyst surface is approximately 4, suggesting that O2 can be efficiently and completely reduced to OH on the RDTeNC surface. - . Figure 5 (d) shows the current change of the catalyst over time after 8 hours of operation at 0.7V. The results indicate that RDTeNC exhibits significantly better electrochemical stability than commercial Pt / C catalysts. These electrochemical results confirm that the synergistic effect of ammonium oxalate and tellurium powder can significantly impart excellent oxygen reduction electrocatalytic performance to rapeseed straw-derived carbon.
[0045] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst, characterized in that, Includes the following steps: (1) After crushing the rapeseed straw, mix it with water and place it in a sealed container for heat preservation treatment. Then take it out, wash and dry it to obtain carbonaceous solid product. (2) The carbonaceous solid product is mixed with tellurium powder and then subjected to a first pyrolysis treatment; (3) The product after the first pyrolysis treatment is mixed with ammonium oxalate and subjected to a second pyrolysis treatment to obtain the electrocatalyst.
2. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The mass ratio of rapeseed straw to water in step (1) is 1:
25.
3. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The temperature of the heat preservation treatment in step (1) is 185-195℃, and the heat preservation time is 12-24h.
4. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The mass ratio of the carbonaceous solid product to tellurium powder in step (2) is 1: (0.5-1.5).
5. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The conditions for the first pyrolysis treatment in step (2) are to raise the temperature to 500°C under nitrogen protection and maintain it for 0.5 h.
6. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The mass ratio of the product after the first pyrolysis treatment in step (2) to ammonium oxalate is 1:(1-3).
7. The method for preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to claim 1, characterized in that, The conditions for the second pyrolysis treatment in step (2) are to raise the temperature to 850-1050℃ under nitrogen protection and maintain it for 2 hours.
8. An electrocatalyst prepared by the method of preparing tellurium and nitrogen co-doped rapeseed straw-derived carbon electrocatalyst according to any one of claims 1-7.
9. The application of the electrocatalyst as described in claim 8 as a cathode oxygen reduction catalyst in a fuel cell or a metal-air battery.
Citation Information
Patent Citations
A tellurium-doped oxygen reduction catalyst and its preparation method
CN113437316B
